O06 That's a lot of Primary Syphilis! How local identification of an increase in primary syphilis cases amongst heterosexual males resulted in a targeted system wide response including outreach to vulnerable street sex workers by the Wildflowers project; a primary care GP/CGL (Change Grow Live charity) partnership. (16th June 2022) - McKinnon, Graham; Beesley, Ruth; Weir, Lucille
Abstract : Introduction: We noticed an unusual upsurge in primary syphilis cases presenting to our sexual health clinic from July 2021 over a period of 4 months. We diagnosed 12 cases of primary syphilis in heterosexual men (HSM); compared to 7 cases of primary syphilis in 2020. Methods: Our clinic notified local public health who co-ordinated an effective response including a local public health campaign. Partner notification identified that street sex workers were identified as sexual contacts.. A partnership with the Wildflower project which does health outreach to street sex workers was formed. They delivered bespoke STI testing to this group. A letter raising awareness was sent to local healthcare providers and a bespoke training package on syphilis was delivered to GPs. Results: During a 4 month period, cases consisted of: 14 primary syphilis (12 in HSM), 2 secondary syphilis, 3 early latent syphilis. The Wildflower clinic tested 17 street sex workers and identified one case of infectious syphilis. Close liaison with the Wildflower project enabled the sex worker with syphilis to be treated. Subsequently case numbers have returned to baseline. Discussion: A sexual health clinic has an important role in picking up on local STI outbreaks in a time critical manner. A particular strength of the response was the outreach to vulnerable street sex workers led by the Wildflower project. Without their involvement an infectious case of syphilis in a sex worker would not have been identified. Working alongside similar local outreach projects should be a priority for all sexual health clinics.